Veterinary forensic necropsies: look through an aspect of forensic traumatology - Souza, Natália Freitas de; Sousa, Ranna Taynara dos Reis; Andrade, Sara Letícia dos Santos; Nobre, Akim Felipe Santos; Pereira, Washington Luiz Assunção; Jaques, Adriana Maciel de Castro Cardoso (Brazilian Journal of Veterinary Pathology, 2021)
Forensic veterinary pathology is essential to identify the cause of death of animals with suspicion of abuse, neglect, exogenous intoxication, medical errors, if the lesions were accidental or ante-mortem or in cases where the animal’s identity is needed. It involves several areas that can be used to determine the cause of death in animals, such as traumatology, entomology and toxicology. This work aims to determine the main lesions found in judicial necropsies of animals from the metropolitan region of Belém, qualifying the most prevalent lesions according to the classification in forensic traumatology. The necropsy was performed according to the animal species and using the method of Ghon. The animals were grouping by specie, sex, race and age and it was made a segmentation by vulnerable energy. 33 judicial necropsies (9.06%) were performed between January 2018 and December 2019, including 22 canines (66.7%), seven felines (21.2%), two farm animals (6.1%) and two wild animals (6.1%). Regarding the sex of the animals, in general, 51.51% were males and 45.45% were females. Young dogs and cats represented the highest percentage of cases. Mixed breed dogs were the most prevalent, with 31.8%. In all species, the most prevalent energy was chemical energy, totalling 18 cases. Second, with six cases, mechanical trauma with only canines and felines, in which, only in three were evident the blunt injury. In only one case, the suspicion was of biodynamic energy, with suggestive findings. In conclusion, the forensic necropsy associated with the animal’s history is capable of providing relevant information which assists the pathologist in the search for injuries, its identification and interpretation.